2007
DOI: 10.1523/jneurosci.1914-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic Lesions of the Medial Mediodorsal Nucleus of the Thalamus Disrupt Reinforcer Devaluation Effects in Rhesus Monkeys

Abstract: The mediodorsal thalamus is a major input to the prefrontal cortex and is thought to modulate cognitive functions of the prefrontal cortex. Damage to the medial, magnocellular part of the mediodorsal thalamus (MDmc) impairs cognitive functions dependent on prefrontal cortex, including memory. The contribution of MDmc to other aspects of cognition dependent on prefrontal cortex has not been determined. The ability of monkeys to adjust their choice behavior in response to changes in reinforcer value, a capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
124
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(137 citation statements)
references
References 40 publications
11
124
2
Order By: Relevance
“…The results from multiple reinforcer Pavlovian devaluation tasks in these studies are consistent with the data in the macaque literature, with devaluation performance impaired by MD lesions in monkeys which have been previously exposed to different reward contingencies (Izquierdo & Murray, 2004b;Mitchell et al, 2007), although neither macaque experiment used an explicitly Pavlovian task prior to operant devaluation. The present data are in conflict, however, with those of Corbit and colleagues (2003), who found that naïve rats are impaired in a multiple reinforcer operant devaluation task.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results from multiple reinforcer Pavlovian devaluation tasks in these studies are consistent with the data in the macaque literature, with devaluation performance impaired by MD lesions in monkeys which have been previously exposed to different reward contingencies (Izquierdo & Murray, 2004b;Mitchell et al, 2007), although neither macaque experiment used an explicitly Pavlovian task prior to operant devaluation. The present data are in conflict, however, with those of Corbit and colleagues (2003), who found that naïve rats are impaired in a multiple reinforcer operant devaluation task.…”
Section: Discussionsupporting
confidence: 87%
“…There does not appear to be a simple dichotomy in which the first task a rat learns is sensitive to outcome devaluation regardless of whether MD is intact and all subsequent tasks are sensitive to devaluation only in rats with MD intact. It appears that there may be a requirement for a change in associative contingencies in order for MD to be required for devaluation.The results from multiple reinforcer Pavlovian devaluation tasks in these studies are consistent with the data in the macaque literature, with devaluation performance impaired by MD lesions in monkeys which have been previously exposed to different reward contingencies (Izquierdo & Murray, 2004b;Mitchell et al, 2007), although neither macaque experiment used an explicitly Pavlovian task prior to operant devaluation. The present data are in conflict, however, with those of Corbit and colleagues (2003), who found that naïve rats are impaired in a multiple reinforcer operant devaluation task.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…There was inconsistent evidence of a delay-dependent impairment (Mumby et al 1993). The results suggest that a major effect of medial dorsal lesions is not on object recognition per se but rather on other aspects of task acquisition and performance, such as sensitivity to the reinforcement contingency (McAlonan et al 1993;Mitchell et al 2007).…”
Section: Medial Dorsal Thalamic Nucleusmentioning
confidence: 84%
“…A more detailed description of the surgical methods and preoperative and postoperative drug treatments was provided by Mitchell et al (2007a). Briefly, each monkey was sedated on the morning of surgery with both ketamine and xylazine and then intubated and, during surgery, was mechanically ventilated and maintained deeply anesthetized using both gaseous [sevoflurane (1.4 -3.0%, to effect, in 100% oxygen)] and intravenous [alfentanil (0.5-3.0 g/kg)] anesthesia.…”
Section: Surgical Proceduresmentioning
confidence: 99%